Metabolic profile of women with PCOS in Brazil : a systematic review and meta-analysis - Spritzer, Poli Mara (2021)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disease affecting women of reproductive age and associated with reproductive and metabolic dysfunction. Few studies are available regarding metabolic traits in Brazilian women with PCOS. The aim of this systematic review and meta-analysis was to summarize the available evidence regarding metabolic traits and comorbidities in Brazilian women with polycystic ovary syndrome (PCOS). Methods: We systematically searched PubMed, Cochrane Central Register of Controlled Trials, and Embase for cross-sectional, case–control, or cohort studies focusing on populations of different regions from Brazil, published until July 31, 2019. Studies were selected if they reported PCOS diagnostic criteria. Studies without a control group were included if they presented relevant metabolic data. Results: Of 4856 studies initially identified, 27 were included in the systematic review and 12 were included in the meta-analysis, for a total of 995 women with PCOS defined by Rotterdam criteria and 2275 controls from different regions of Brazil. Obesity, metabolic syndrome and IGT were prevalent, and standard mean differences for BMI (SMD 0.67, 95% CI, 0.29, 1.05), waist circumference (SMD 0.22, 95% CI 0.02, 0.41), systolic (SMD 0.66, 95% CI 0.30, 1.01) and diastolic blood pressure (SMD 0.55, 95% CI 0.24, 0.87), glucose (SMD 0.21, 95% CI 0.04, 0.38) and HOMA (SMD 0.78, 95% CI 0.52, 1.04) were significantly higher in Brazilian women with PCOS compared to controls. Lipid profile was more adverse in PCOS vs. non-PCOS women. Between-study heterogeneities were low/moderate for glucose and HOMA and moderate/high for the other variables. Conclusions: The data of this systematic review and meta-analysis indicate that Brazilian women with PCOS have a worse metabolic profile than women without PCOS with no important regional differences. The prevalence of metabolic changes is intermediate in Brazil vs. other countries.